The fish diversity of mangrove waters in Lombok Island, West Nusa Tenggara, Indonesia - GEMA WAHYUDEWANTORO (Biodiversitas Journal of Biological Diversity, 2018)
Wahyudewantoro G. 2018. The fish diversity of mangrove waters in Lombok Island, West Nusa Tenggara, Indonesia. Biodiversitas 19: 71-76. Lombok Island’s waters are the main gateway of the mass water flow from the Pacific and Indian Oceans. Therefore, it is suspected the fish species that inhabit them is very diverse. The aim of the research was to reveal the diversity of mangrove fish species, with a case study in West Lombok and Central Lombok. Fishes were caught using cast net with mesh sizes of 1.5 cm and 2.5 cm, gill net with mesh sizes of ¾ inch, 1.5 inch and 2 inches. This research found 38 species belonging to 28 genera and 20 families. Oryzias javanicus and Periopthalmus argentilineatus were distributed at all research stations.Species diversity index (H) of fish was in the range of 2.618 to 3.072, evenness index (E) 0.803 to 0.950 and species richness index (d) from 4.328 to 6.206. Based on the similarity of fish species that exist in each station, the species of fish in station IV were different from those of other stations.